Citizen participation in the criminal justice: ¿Democratization or useless ornament of the courts? - Brandt, Hans-Jürgen (2015)
With the implementation of the new criminal procedure code, profound changes have taken place in the criminal justice system therefore judge the procedural activity of the inquisitorial system changes to accommodate a judge's factual decision on the prosecution and may be supported by citizen judges, called jurors, who are not lawyers but ordinary citizens because they would have to do their capacity, their life experience and common sense to the deliberations and decisions of the court.